PRINCIPLES OF RECREATING POETIC IMAGES IN POETRY TRANSLATION - Ogulsaltan Khalmuratova (International Journal of Literature and Language Studies, 2026)
Annotation: This article theoretically studies the problems of recreating artistic imagery in the translation of a poetic work, preserving rhythm and tone in it. Also, with a focus on Uzbek-Turkmen literary ties and mutual translation traditions, translations of the poems of the Turkmen poet Gara Seytliyev into the Uzbek language were subjected to scientific and theoretical analysis through specific examples.